KEDUDUKAN DAN HAK ANAK HASIL ZINA DALAM PERSPEKTIF HUKUM ISLAM - Gusdira Yoga Sabrani; Nadhirotul Triana; Desmi Satriana (STAI Nurul Falah Airmolek, 2026)
This article discusses the legal and moral status of children born out of wedlock from the perspective of Islamic law. The focus includes the definition of children born from zina, their legal standing in Islamic jurisprudence, and the rights guaranteed to them despite the circumstances of their birth. This study uses a conceptual approach based on classical and contemporary Islamic literature. The findings show that Islamic teachings do not place the burden of sin on the child, and their fundamental rights must be protected. The study highlights the need for social awareness to avoid discrimination against children born from non-marital relations.